2013
DOI: 10.1111/j.1445-5994.2011.02565.x
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict sputum eosinophilia from clinical assessment in patients referred to an adult asthma clinic?

Abstract: This study demonstrates that the serum eosinophil count and FEV(1) combined with aspects of a clinical history may provide a simple and practical alternative to assessment of airway (sputum) eosinophilia in the clinical setting. A full blood count can be performed at a substantially lesser cost and with greater accessibility than induced sputum. We feel the time has come for the clinical utility of the serum eosinophil count to be revisited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…We found that the peripheral eosinophil count is able to identify the presence of eosinophilic phenotype with low accuracy in unselected adult asthmatics and with moderate accuracy in selected adult asthmatics who are steroidnaïve without atopy (AUC=0.809). Consistent with the previous study (15,16,22), we also found that there is a significant positive association between the peripheral eosinophil count and sputum eosinophil count. The study by Nadif et al showed that peripheral eosinophils and neutrophils had the ability to distinguish asthmatics into four inflammatory patterns with remarkable phenotypic characteristics (23).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that the peripheral eosinophil count is able to identify the presence of eosinophilic phenotype with low accuracy in unselected adult asthmatics and with moderate accuracy in selected adult asthmatics who are steroidnaïve without atopy (AUC=0.809). Consistent with the previous study (15,16,22), we also found that there is a significant positive association between the peripheral eosinophil count and sputum eosinophil count. The study by Nadif et al showed that peripheral eosinophils and neutrophils had the ability to distinguish asthmatics into four inflammatory patterns with remarkable phenotypic characteristics (23).…”
Section: Discussionsupporting
confidence: 82%
“…The study by Nadif et al showed that peripheral eosinophils and neutrophils had the ability to distinguish asthmatics into four inflammatory patterns with remarkable phenotypic characteristics (23). Their study also supported that the peripheral eosinophil count might be an effective surrogate of sputum to distinguish asthma inflammatory phenotypes (22).…”
Section: Discussionmentioning
confidence: 49%
“…In asthma, sputum eosinophil count correlates with blood eosinophil count [4,[6][7][8] and blood eosinophil count is considered as a good surrogate marker for sputum eosinophil count (over 2-3% with a cut-off of 220 cells per mm 3 or 3%) [4,9]. However, the sensitivity and specificity of blood eosinophils to predict a sputum eosinophil proportion of o3% are ,80%, and there are patients who show discordance between local and systemic inflammation.…”
Section: Introductionmentioning
confidence: 98%
“…Clearly, readily accessible biomarkers which accurately predict airway inflammation are needed for managing difficult-to-treat asthma, and to serve as response endpoints in clinical trials testing and registering new biologic therapies for asthma. Thus, more accessible biomarkers are employed as surrogates for sputum inflammatory cell measurements in clinical studies without first establishing their accuracy across the full range of asthma or severity subphenotypes 13-14 .…”
Section: Introductionmentioning
confidence: 99%